Tactile pad for the presentation of tactile sensation from moving pictures - Hideyuki Sawada (2018)
An innovative tactile pad that presents various tactile sensations synchronizing with moving pictures is presented in this paper. To display tactile/touch sensations from a pad, a tactile display panel is designed by employing 10 micro-vibration actuators that provide tactile-stimulation sources using shape memory alloy wires. With the employment of the human higher-level perception caused by appropriate micro-vibratory stimuli, the resolution of the designed tactile display panel increases more than three times, so that people perceive various tactile sensations with high resolution enough for the better reality. By employing a webcam to capture moving pictures, the tactile pad system automatically recognizes the texture information contained in the scene, which are associated with tactile information to be output from the tactile pad. In order to let people reasonably perceive the presented tactile sensations, the developed system automatically translates visual information to tactile sensation. For verifying the effectiveness of the developed vision-based tactile pad system, experiments are conducted and the results are presented. © 2014 IEEE.